2020
DOI: 10.1371/journal.pone.0230015
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the faecal microbiota of horses and ponies during a two-year body weight gain programme

Abstract: Obesity is a major health concern in many domesticated equids animals since it is related to metabolic abnormalities such as insulin dysregulation, hyperlipidaemia or laminitis. Ponies especially are known as "easy keepers" and are often affected by obesity and its related metabolic disorders. Research in the last decade indicated that the intestinal microbiota may play an important role in the development of obesity, at least in humans. Therefore, the objective of our study was to characterize changes in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 56 publications
2
6
0
Order By: Relevance
“…Therefore, we evaluated differences in microbiota composition between horses and ponies in our study. We found no differences in alpha-diversity between horses and ponies, which is in line with a recently published study [49]. However, a significant difference in beta-diversity was observed when horses and ponies were compared, demonstrating significant differences in microbiota composition.…”
Section: Horse Typesupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, we evaluated differences in microbiota composition between horses and ponies in our study. We found no differences in alpha-diversity between horses and ponies, which is in line with a recently published study [49]. However, a significant difference in beta-diversity was observed when horses and ponies were compared, demonstrating significant differences in microbiota composition.…”
Section: Horse Typesupporting
confidence: 92%
“…For Acidaminococcaceae, Rikenellaceae and P-251-o5, we observed that specific genera/species within these families increase or decrease according to horse type, suggesting that bacterial shifts occur within these families. In the study by Langner et al (2020), Ruminococcaceae, Rikenellaceae, F082 and Bacteroidales UCG-001 were found to be more abundant in ponies compared to horses, but only after all subjects included in the study were kept on a 200% net energy requirement diet for two years [49]. The differences, therefore, not only reflect differences between ponies and horses, as they were not present at the start of the study but are heavily influenced by the high energy diet.…”
Section: Horse Typementioning
confidence: 94%
“…The equine intestinal bacterial community has been extensively studied, and it is now considered to influence horse organism homeostasis and health, to the same extent as bacteria in the human gut (reviewed in [36] , [59] , see also [60] , [61] . The equine gut bacterial community is involved in the pathology of specific diseases such as equine metabolic syndrome and laminitis [62] .…”
Section: Discussionmentioning
confidence: 99%
“…In a recent equine 2-year weight gain study looking into the effect of obesity on the equine fecal microbiome, a significant increase of the relative abundance of the phylum Firmicutes was shown to be associated with increased body weight, body condition score, and cresty neck score. In addition, the phyla Bacteroidetes and Spirochaetes both decreased in relative abundance in horses and ponies with an increase in obesity, although these differences were not significant ( 117 ). Assuming that these horses developed insulin dysregulation while gaining weight, this fecal microbiome change is in accordance with our data as well: with increasing insulin sensitivity, the relative abundance of the phyla Bacteroidetes and Spirochaetes is increased, and the relative abundance of the phylum Firmicutes is decreased.…”
Section: Discussionmentioning
confidence: 99%